A comparative retrospective study of different surgical guide designs for static computer‐assisted implant surgery in posterior single edentulous sites. Issue 1 (11th October 2021) - De Souza, Andre Barbisan; Kang, Michael; Negreiros, William Matthew; El‐Rafie, Khaled; Finkelman, Matthew; Papaspyridakos, Panos
Abstract: Aim: The aim of this retrospective clinical study was to compare the accuracy of static Computer‐assisted implant surgery (sCAIS) in posterior single edentulous patients using different surgical guide designs. Materials and Methods: Thirty‐seven partially edentulous patients with a total of 54 implants were included in the study. Seventeen implants were included in Group 1—Unbounded Tooth‐Mucosa Supported; 18 implants in Group 2—Unbounded Tooth Supported; and 19 implants in Group 3 (Control)—Bounded Tooth Supported. All partially edentulous patients were treated with fully guided implant surgery using the corresponding surgical guide. Discrepancies between the pre‐planned and post‐operative implant position were evaluated. Results: The mean angular deviation ± standard deviation (SD) was 2.91 ± 1.56°, 3.33 ± 1.72° and 2.25 ± 1.13° for Groups 1, 2, and 3, respectively. The mean ± SD 3D offset at base was 0.66 ± 0.29 mm, 0.77 ± 0.24 mm, and 0.49 ± 0.22 mm; and 3D offset at tip was 0.84 ± 0.45 mm, 1.07 ± 0.38 mm, and 0.75 ± 0.25 mm for Groups 1, 2, and 3, respectively. No statistically significant differences between groups were found for angular deviation. There were statistically significant differences between Groups 2 and 3 for 3D offset at base ( p = .002) and 3D offset at tip ( p = .010). Conclusions: Different surgical guide designs for posterior single edentulous areas appear to be associated with the accuracy level of sCAIS. In unbounded sites, having additional posterior attached soft tissue support is preferable.